Primary hepatic neuroendocrine neoplasms: imaging characteristics and misdiagnosis analysis - Yang, Xiu-Rong; Li, Ying-Li; Li, Zi-Yan; Chai, Xiao-Ming (Frontiers in Oncology, 2024)
Objective To analyze the CT and MR features of Primary hepatic neuroendocrine neoplasms (PHNENs) in order to enhance the diagnostic accuracy of this disease. Methods A retrospective analysis was conducted on patients diagnosed with hepatic neuroendocrine neoplasms, excluding other sites of origin through general examination and postoperative follow-up. The CT and MR signs were analyzed according to the 2018 version of Liver Imaging Reporting and Data System (LI-RADS), along with causes of misdiagnosis. Results Twelve patients, including 6 males and 6 females, were enrolled in this study. There was no significant increase in liver tumor markers among all cases. Most masses were multiple (9/12), exhibiting low attenuation on pre-contrast CT scans, T1-hypointense signal, T2-hyperintense signal, and restricted diffusion. The majority of these masses (7/10) demonstrated similar rim arterial phase hyper-enhancement as well as peripheral "washout" during venous portal phase and delayed phase imaging. Three cases had incomplete capsules while one case had a complete capsule. Cyst/necrosis was observed in 7 out of all cases following administration of contrast agent, with 5 mainly distributed in the periphery. All masses lacked fat, calcification, vascular or bile duct tumor thrombus formation. Conclusion The imaging findings associated with PHNENs possess certain specificity, often presenting as multiple masses within the liver accompanied by peripheral cyst/necrosis, similar rim arterial phase hyper-enhancement during venous portal phase and delayed phase imaging.